Algebra problems tend to be worded a little differently from the typical 'Ann had a dozen apples' kind of arithmetic questions. Algebra deals with variables and numbers which are arranged in equations to form generalizations. Hence the terms used are understandably a bit different in order to convey the relation between different elements. Algebra word problems require students to decipher the meaning and form the correct equations. **Algebra word problem solver** is an online tool which will help users understand how algebra word problems are stated. With the word problem solver for algebra, students learn what the different terms mean and what kind of relation they imply.

Online algebra word problem solvers are available for all grades and levels of algebra. Algebra 1 word problem solvers and algebra 2 word problem solvers cover the beginner and intermediate levels of algebra. Free algebra word problem solvers also give you tips and hints on which terms or phrases to look out for. Learning to identify these will enable you to understand what you are expected to find out much quicker. College algebra word problem solvers are designed to handle the advanced course load and are very popular among college students who turn to the internet for a substantial amount of course help and research.

Let the altitude of the triangle = x

therefore, base of the triangle = 2 + 2x

Given, area of the triangle = 30

Step 1:

Area of the triangle = $\frac{1}{2}$ Base * Height

=> 30 = $\frac{1}{2}$ * (2 + 2x) * x

=> 30 * 2 = (2 + 2x) * x

=> 60 = 2x + 2x^{2}

=> 2x^{2} + 2x - 60 = 0

Step 2:

Solve for x, 2x^{2} + 2x - 60 = 0

=> 2x^{2} + 12x - 10x - 60 = 0

=> 2x(x + 6) - 10(x + 6) = 0

=> (2x - 10)(x + 6) = 0

**Step 3:**

either 2x - 10 = 0 or x + 6 = 0

=> 2x = 10 or x = - 6

Length must be positive, so neglect x = - 6.

=> 2x = 10

=> x = 5

Hence altitude of the triangle is 5 m**. answer**

therefore, base of the triangle = 2 + 2x

Given, area of the triangle = 30

Step 1:

Area of the triangle = $\frac{1}{2}$ Base * Height

=> 30 = $\frac{1}{2}$ * (2 + 2x) * x

=> 30 * 2 = (2 + 2x) * x

=> 60 = 2x + 2x

=> 2x

Step 2:

Solve for x, 2x

=> 2x

=> 2x(x + 6) - 10(x + 6) = 0

=> (2x - 10)(x + 6) = 0

either 2x - 10 = 0 or x + 6 = 0

=> 2x = 10 or x = - 6

Length must be positive, so neglect x = - 6.

=> 2x = 10

=> x = 5

Hence altitude of the triangle is 5 m

Let the age of the son = x years

Therefore the age of the father = 45 - x

(Sum of their ages is 45)

Step 1:

5 years ago:

Son's age = x - 5

and father's age = 45 - x - 5 = 40 - x

Step 2:

The problem states:

Father's age = 3 + 3(Son's age)

=> 40 - x = 3 + 3(x - 5)

=> 40 - x = 3 + 3x - 15

=> 40 - x = 3x - 12

=> 3x + x = 40 + 12

=> 4x = 52

Divide each side by 4

=> x = $\frac{52}{4}$

=> x = 13

Son's present age = 13 years

=> After 4 years son will be of = 13 + 4 = 17 years.

Therefore the age of the father = 45 - x

(Sum of their ages is 45)

Step 1:

5 years ago:

Son's age = x - 5

and father's age = 45 - x - 5 = 40 - x

Step 2:

The problem states:

Father's age = 3 + 3(Son's age)

=> 40 - x = 3 + 3(x - 5)

=> 40 - x = 3 + 3x - 15

=> 40 - x = 3x - 12

=> 3x + x = 40 + 12

=> 4x = 52

Divide each side by 4

=> x = $\frac{52}{4}$

=> x = 13

Son's present age = 13 years

=> After 4 years son will be of = 13 + 4 = 17 years.